Penyisihan Logam Mangan (Mn) Dalam Air Tanah Pada Proses Aerasi Menggunakan Kombinasi Cascade Aerator Dan Arang Aktif - Davin Zamora Putra; Edward HS; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Levels of Mn are metals in the ground water. The high levels of Mn in ground water can be processed using either advanced technology or simple technology. One technology that can be applied to set aside Mn is aeration. Aeration is the addition process of oxygen into the water to make oxidation reaction of Mn which then will cause sediment MnO2. The aim of this research is to study the cascade aerator ability in removing Mn levels in groundwater with variation of discharge 50, 60, 70, 80, 90 ml/s and the addition of activated carbon. Then calculate the value of gas transfer coefficient (KLa) in aeration process using cascade aerator. Mn levels before aeration of 0.4 mg/l for Mn. The results showed that the highest removal efficiency of Mn occurred at optimum discharge 90 ml/s using activated carbon with efficiency of 99,2%. While the lowest efficiency occurred at 50 ml/s discharge without activated carbon with efficiency of 94.6%. As well as the highest gas transfer coefficient value obtained in the experiments of 90 ml/s of 0.046/min.Keywords: aeration, cascade aerator, manganese (Mn), activated carbon, discharge, gas transfer coefficient (KLa)